'Adaptive accumulation' and US political economy. Issue 5 (3rd September 2017) - Loeppky, Rodney
ABSTRACT: According to popular and academic understandings of political economy, the United States is characterised by the most open forms of free market production. From Marxist to institutionalist to liberal analyses, the US is said to exhibits a governance model in which state structures are minimally intrusive to capitalist civil society. There is a need for political economy that re-positions the US state as more than just a willing facilitator, lender-of-last-resort or minimal regulator of capitalist dynamics. This paper argues that 'adaptive accumulation' has normalised in the US context, wherein capital actively allies itself with public state objectives (and mechanisms) to seek new or enhanced profit streams, by transforming or rerouting public revenues, such that they afford private accumulation. The robust entry of capital in areas such as health, education and incarceration are highly notable, inasmuch as they harness public objectives for private but not-so-competitive ends. By shedding light on such domains, the paper contributes to our understanding of capital and its ongoing efforts to stay ahead of investment crises by actively shaping its operative environment – in this case, maintaining both the credibility and regularity of publicly inspired (and often financed) revenue streams while, ultimately, transforming their utilisation and purpose.